Pola distribusi penderita benjolan tiroid di RSU Wonosari, Gunungkidul - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
ABSTRAK During 1988 - 1990 121 patients with thyroid nodules at the Surgery Unit of the Wonosari General Hospital were operated. Most of them (90%) were female aged 12 to 70 years. The patients came from all Sub-districts of the Gunungkidul District and also from three adjacent Sub-districts of the Wonogiri District. The laboratory diagnoses were colloid goiter (85%), adenoma (9.1%), carcinoma (4.9%) and only one (0.8%) had Hashimoto struma. The overall clinical diagnosis error was 11.9% and clinical prognosis error was 1.7%.